2018
DOI: 10.5812/iranjradiol.56115
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Diffusion Kurtosis Imaging in Mild Traumatic Brain Injury

Abstract: Background: Traumatic brain injury (TBI) can result from blunt trauma or acceleration/deceleration force and is considered to be one of the most important public health problems. Many patients of TBI lose professional competence and independence. They may eventually suffer serious sequelae, such as cognitive impairment, memory loss, and long-term headache. In craniocerebral trauma patients, mild traumatic brain injury accounts for 70% -80% of the cases. Early diagnosis and intervention can decrease the post-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Diffusion kurtosis imaging (DKI) is an expansion of the tensor model and measures the degree of non-Gaussian diffusion which could provide additional information about tissue heterogeneity or complexity ( Jensen and Helpern, 2010 ). Using DKI, ( Grossman et al, 2013 , 2012 ) and ( Zhang et al, 2018 ) found reductions in MK in mTBI patients that were associated with cognitive impairments. However, DTI and DKI are only representations of the diffusion signal and aim to characterise the probabilistic water displacement profile without microstructural specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion kurtosis imaging (DKI) is an expansion of the tensor model and measures the degree of non-Gaussian diffusion which could provide additional information about tissue heterogeneity or complexity ( Jensen and Helpern, 2010 ). Using DKI, ( Grossman et al, 2013 , 2012 ) and ( Zhang et al, 2018 ) found reductions in MK in mTBI patients that were associated with cognitive impairments. However, DTI and DKI are only representations of the diffusion signal and aim to characterise the probabilistic water displacement profile without microstructural specificity.…”
Section: Introductionmentioning
confidence: 99%